2013
DOI: 10.1002/ijc.28402
|View full text |Cite
|
Sign up to set email alerts
|

Case–case comparison of smoking and alcohol risk associations with Epstein–Barr virus‐positive gastric cancer

Abstract: Helicobacter pylori is the primary cause of gastric cancer. However, monoclonal Epstein-Barr virus (EBV) nucleic acid is also present in up to 10% of these tumors worldwide. EBV prevalence is increased with male sex, non-antral localization and surgically disrupted anatomy. To further examine associations between EBV and gastric cancer, we organized an international consortium of 11 studies with tumor EBV status assessed by in situ hybridization. We pooled individual-level data on 2,648 gastric cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 32 publications
3
36
3
Order By: Relevance
“…Approximately 990,000 people around the world are diagnosed with GC each year, of whom about 738,000 die from this disease [2]. Helicobacter pylori infection is the primary cause of GC incidence, and several lifestyles are independently associated with GC risk, such as alcohol, smoking, and weight [3,4]. Curative surgeries and adjuvant chemotherapies are considered as acceptable intervention for GC treatment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 990,000 people around the world are diagnosed with GC each year, of whom about 738,000 die from this disease [2]. Helicobacter pylori infection is the primary cause of GC incidence, and several lifestyles are independently associated with GC risk, such as alcohol, smoking, and weight [3,4]. Curative surgeries and adjuvant chemotherapies are considered as acceptable intervention for GC treatment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Camargo et al [14] recently reported that smoking is a risk factor for EBVaGC (odds ratio of 1.5; 95% CI 1.01-2.3). The frequency of Helicobacter pylori infection is controversial; some reports indicate less frequent H. pylori infection in EBVaGC [15,16], while others indicate that the infection frequency is higher in EBVaGC than in other gastric cancers [17,18].…”
Section: Epidemiological Clinical and Pathological Features Of Ebvagcmentioning
confidence: 99%
“…High salt intake is a proven risk factor and high salt intake is also common in our population. Smoking has also been shown to have an impact; more on EBV related than non EBV related gastric cancers (Camargo et al, 2014). H. pylori infection is a common infection among our population (Chong VH et al, 2009) and this may attenuate the impact of EBV on gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…However, earlier cases showed more lymphocytic infiltrations consistent with what have been reported in the literature. A recent large multi-center study reported that EBVaGC tended to have lower tumor-node-metastasis based on the TNM staging system and EBV positivity was associated with better survival (Camargo et al, 2014). Although, studies have shown that EBV lead to molecular changes resulting in gastric carcinogenesis, different to that of H. pylori sequence, and that there are certain characteristics that are unique to EBVaGC, there are still differences and conflicting results based on studies from other populations.…”
Section: Discussionmentioning
confidence: 99%